Green and facile fabrication of nano-ZnO coated cellulose/starch/activated carbon hydrogel for enhanced dyes adsorption and antibacterial activity. (December 2022) - Zhang, Xingming; Liu, Qiang; Zhu, Siming; Yu, Ming
Abstract: Water shortages and pollution have become the most pressing problems to solve today. Herein, a green and antibacterial hydrogel, Sugar Beet Pulp Cellulose/Starch/Activated Carbon-ZnO (C/S/AC-ZnO) was prepared by crosslinking and ultrasonic cavitation. The structure and properties of hydrogels were characterized by SEM, FTIR, XRD, and TG. For methylene blue and methyl orange, the hydrogel's highest adsorption capacities were 142.70 mg/g and 72.63 mg/g, respectively. The adsorption results showed that the hydrogels have excellent adsorption performance on methylene blue and methyl orange, especially for methylene blue. The adsorption process of dyes was more consistent with the pseudo-second-order kinetic model and the Langmuir isothermal adsorption model. The adsorption process was an endothermic reaction, and the moderately increasing temperature was beneficial to the adsorption reaction. Furthermore, after 5 cycles of adsorption and desorption, the adsorption properties of methylene blue and methyl orange on C/S/AC3.0-ZnO remained 91.22 % or 90.44 %, respectively. The hydrogels loaded with ZnO by ultrasonic cavitation exhibited excellent antibacterial ability. C/S/AC3.0-ZnO had a 2.83 times greater antibacterial impact on E. coli than on S. aureus. While adsorbing pollutants, the hydrogels can further sterilize the water body and protect its structure from microbial damage and realize recycling. Graphical Abstract: ga1 Highlights: Green Urea-Alkali and ultrasonic cavitation methods were used to fabricate the eco-friendly composite hydrogel. Composite hydrogel had excellent adsorption effect on methylene blue and methyl orange, especially for methylene blue. Nano-ZnO endowed hydrogel adsorbent excellent antibacterial ability. The adsorption capacity of composite hydrogel maintained above 90 % after 5 cycles.